Fine Scale Phylogeography of Urban Western European Hedgehog Erinaceus europaeus in South‐East England - Jessica Turner; Chris Carbone; Becki Lawson; Katharina Seilern‐Macpherson; Chris Faulkes (Ecology and Evolution)
ABSTRACT Preserving genetic diversity within species and populations is an important conservation goal, yet observed genetic structure can be influenced by both contemporary and historical processes. Here, we investigate the phylogeography of the western European hedgehog (Erinaceus europaeus) in Greater London, east and south‐east England, using DNA sequence analysis of a section of the mitochondrial cytochrome b gene and control region. We find seven haplotypes within the study region, of which six are novel, indicating higher diversity than previously identified in the UK. Comparison with published haplotypes from mainland Europe identified low sequence divergence from those found in France and Jersey. Most haplotypes were widespread within south‐east England, in contrast to strong spatial clustering of haplotypes seen at broader scales across Europe. However, local haplotype diversity varied within the study region, with some evidence supporting the view that genetic isolation has led to an absence of haplotypes in urban sites in central London. Broader UK‐wide sampling is recommended to ascertain whether additional haplotype lineages and geographic structuring exist at larger spatial scales in the UK. These findings may have important considerations for future hedgehog conservation efforts.